The Effect of Implementation Arabic Vocabulary Repetition Punishment on Grade VII Students of Jauharul Wathon Islamic Boarding School in Muaro Jambi - Helty, Helty; Iryani, Eva; Harahap, Alvie Rahmadani; Mustika, Maharani; Pratama, Aldo; Nursaid, Alam (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2023)
This research aims to determine the application of punishment in the learning process of students in class VII at the Islamic Boarding School, Jauharul Wathon Muaro Jambi, especially in the Arabic language learning process. Furthermore, this research tries to see what impact arises from giving punishment for repeating vocabulary on the Arabic language learning process of class VII students at the Islamic Boarding School Jauharul Wathon, Muaro Jambi. The type of research used in this research is qualitative research with a descriptive approach, and in the data collection process, the author uses observation, documentation, and interview methods. The subjects in this research were class VII Arabic language education teachers at the Islamic Boarding School, Jauharul Wathon, and Muaro Jambi. The research results show several positive and negative factors in implementing the impact of punishment for repeating vocabulary on class VII students at the Islamic Boarding School Jauharul Wathon, and Muaro Jambi. As for the impacts arising from punishment for repeating vocabulary, most of them have a positive impact, and a small part have a negative impact.